Overview of the fertilizer supply chain and market structure in Africa: A cross-country assessment - Hernandez, Manuel A.; Paz, Florencia; Adeoti, Adetola I.; Adong, Annet; Jumbe, Charles B.L.; Lagat, Kiplimo Araap; Kaiyatsa, Stevier (International Food Policy Research Institute, 2018)
Agriculture continues to play an important role in African economies. According to the African Development Bank, agricultural activities comprise around 15 percent of the continent’s gross domestic product (GDP) and agricultural employment represents around 58 percent of total employment in Sub-Saharan Africa. The region’s population is expected to double to 2 billion people by 2050. Along with expected income growth, the population increase will lead to a substantial rise in food requirements. To meet food demand, FAO estimates that agricultural production would have to increase 112 percent between 2013 and 2050. Meeting this demand will not be easy, as agricultural productivity in SSA remains low and shows slow growth. The vast majority of African smallholder farmers produce low-yield food crops using a minimal set of inputs. Inadequate access to improved inputs such as fertilizers presents a major constraint for smallholders. In the region, more nutrients are removed with harvested crops than are applied with fertilizer or manure, resulting in unsustainable soil nutrient depletion. Improved fertilizer use will help to counteract this trend while substantially improving food security.